Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis